Spline Methods for a Class of Singularly Perturbed Boundary Value Problems - Ogunlaran, O.M; Taiwo, O.A (International Journal of Mathematical Research, 2013)
In this paper, we develop numerical methods based on a non-polynomial spline function with uniform grid for solving certain class of singularly perturbed boundary value problems. The proposed methods are second-order and fourth-order accurate. Numerical examples are provided to demonstrate the efficiency of the proposed methods.